Comparative evaluation of FAT, IS900 PCR and microscopy vis-a-vis histopathology for the detection of Mycobacterium avium subsp paratuberculosis infection in tissues of goats naturally died in herds endemic for Johne’s disease - CHATURVEDI, SHIVAM; SINGH, SHOOR VIR; SRIVASTAVA, ASHOK KUMAR; GANGWAR, NEERAJ KUMAR; KUMAR, NAVEEN; RAWAT, KRISHNA DUTTA; GUPTA, SAURABH; CHAUBEY, KUNDAN KUMAR; SINGH, RAJENDRA; SINGH, RAGHAVENDRA; DHAMA, KULDEEP (The Indian Journal of Animal Sciences, 2017)
Study investigated infection of Mycobacterium avium subspecies paratuberculosis (MAP) in paired tissues viz. ileum and mesenteric lymph nodes (MLN) from 74 goats using histopathology, acid fast staining of tissue sections, fluorescent antibody test (FAT), IS900 tissue PCR and culture. Histopathology of H&E stained tissue sections revealed variable grades of lesions of Johne’s disease (JD) in 37 (50.0%) ileae and 21 (28.4%) MLN. In AFB staining, 16 (21.6%) intestine and 10 (13.5%) MLN revealed presence of acid fast bacilli indistinguishable to MAP. Thirteen (17.5%) intestine and 9 (12.1%) MLN were positive in FAT. Eleven (14.8%) intestine and 7 (9.4%) MLN were positive by IS900 tissue PCR, whereas 7 (9.5%) intestine and 8 (10.8%) MLN were positive in culture. The study showed that sensitivity of histopathology (H&E staining) was highest as compared to other routine tests for the diagnosis of MAP infection in tissues of goats died (irrespective of cause of deaths) during study period from goat herds endemic for Johne’s disease. Lower sensitivity of FAT than histology was due to the strong cell mediated immunity exhibited by MAP. Though difference was not significant between sensitivities of FAT and PCR, FAT and AFB staining, and agreement was very good; however, results of the study suggested, that FAT may be a useful test to improve the diagnostic efficacy of caprine Johne’s disease and more effective in the detection of grade I lesions as compared to culture and PCR. Study also showed that it was essential to collect both tissues (intestines and MLNs) for the diagnosis of MAP infection at necropsy.